An ant-colony approach for the design of optimal chunk scheduling policies in live peer-to-peer networks. (1st January 2013) - Romero, Pablo; Robledo, Franco; Rodríguez-Bocca, Pablo
Peer-to-peer networks are self-organised communities over the internet infrastructure, in which peers are both clients and servers. The global resources of a peer-to-peer network increase proportionally with the population, promoting scalability. Peers are organised covering neighbouring-strategies and chunk-scheduling policies that determine the success of the cooperation scheme. In this paper, we address the design of chunk-scheduling policies in a cooperative scenario, assuming a complete mesh-topology under regime. All users wish to display a video channel with no cuts and low buffering times. We propose an in-depth analysis of this cooperative system, and develop the best chunk scheduling policy so far, found via a sophisticated ant-colony-based exploration. We introduce the new policy into a real platform. There, users wait five seconds to start watching following our new policy (versus minutes in previous policies), with acceptable number of cuts.